Cytocompatibility, stability and osteogenic activity of powder metallurgy Ta-xZr alloys as dental implant materials. (February 2021) - Ou, Pinghua; Liu, Jue; Hao, Cong; He, Rengui; Chang, Lin; Ruan, Jianming
Tantalum (Ta) and zirconium (Zr) alloys were found to had low elastic modulus and similar biomechanical characteristics as the human bone. However, the biocompatibility and osteogenic potential of Ta-xZr alloyswith different proportions (20, 30, 40 and 50% Zr by atom) remains to be investigated. In this study, the biocompatibility of Ta-xZr alloys and commercially pure titanium (cpTi) was evaluated in vitro by cell counting kit-8 assay. The adhesion of MG63 osteoblasts to the surface of the alloys was observed by fluorescence microscopy, and their morphology was analyzed by scanning electron microscopy (SEM). The expressions of alkaline phosphatase (ALP), Ki67, osteocalcin (OC), collagen-I (Col-I) and Integrin β1 mRNA in the cultured cells were determined by RT-PCR. As a result, Ta-xZr (x = 20, 30, 40 and 50 at%) alloys were non-toxic and supported proliferation of the MG63 cells. The osteoblasts adhered to the Ta-xZr alloys, and subsequently spread and proliferated rapidly. Furthermore, the cells grown on Ta-20Zr and Ta-30Zr expressed high levels of ALP, Col I and OC, indicating that the Ta-xZr alloys can induce osteogenesis. In conclusion, Ta-xZr alloys promoted the adhesion, proliferation and osteogenic differentiation of MG63 cells. The Ta-xZr composites with a higher proportion of Ta exhibited superior osteogenic activity, and Ta-30Zr is therefore a promising alternative for Ti implants.